Accessibility analyses of post offices in Germany differentiated by means of transport using a grid-based model - Inga Tegetmeyer; Stefan Neumeier (Johann Heinrich von Thünen-Institut, 2024)
Urbanization and demographic change are also having an impact on the demand for basic services. As a result, private and public service providers are gradually abandoning economically unattractive locations, whereby rural areas are generally more affected by these developments than urban areas. Against the backdrop of the norma-tive political goal of maintaining equivalent living conditions in all parts of the country, an important political objective in Germany is to counteract such processes. Unfortunately, apart from a few, usually spatially highly aggregated, supply indicators, there is hardly any small-scale differentiated data below the municipal level that provides information on whether, where and for whom the accessibility of basic services may be problematic. One of the areas for which there is hardly any data to date - although minimum service provision is defined by law - is the postal service. This working paper therefore examines the question of whether, where and, if so, for whom there are spatial inequalities in the accessibility of Deutsche Post AG post offices in Germany. The aim of the working paper is to create a data basis that allows us to assess the basic accessibility of Deutsche Post AG post offices, as it appears to households, for the whole of Germany. To this end, we examined the accessibility of post offices by the various means of transport - foot, bicycle, car and public transport - on a small scale in a 250250 meters analysis grid using a GIS accessibility model from the perspective of the "households". We found that, contrary to popular belief, the accessibility or inaccessibility of post offices in Germany is not so much a spatial phenomenon that favors non-rural regions and disadvantages rural regions, as is often assumed. Instead, our study showed that the accessibility of post offices in Germany depends heavily on people's individual mobility in both rural and non-rural areas. – – Urbansierung und demografischer Wandel zeigen auch Auswirkungen auf die Nachfrage nach Dienstleistungen der Grundversorgung. Das führt dazu, dass private und öffentliche Dienstleister bestrebt sind, wirtschaftlich unattraktive Standorte sukzessive aufgeben, wobei ländliche Räume von diesen Entwicklungen i. d. R. stärker betroffen sind als urbane. Vor dem Hintergrund des normativen politischen Leitbildes der Aufrechterhaltung gleichwertiger Lebensverhältnisse in allen Landesteilen besteht in Deutschland ein wichtiges Politikziel darin, solchen Prozessen entgegenzuwirken. Einer der Bereiche, für die es bislang kaum Daten gibt - obwohl die Mindestversorgung gesetzlich vorgeschrieben ist -, ist die Post. Dieses Thünen Working Paper untersucht daher die Erreichbarkeit von Postfilialen der Deutschen Post AG in Deutschland. Ziel des Thünen Working Papers ist es, eine Datengrundlage zu schaffen, die es erlaubt, die grundlegende Erreichbarkeit von Postfilialen der Deutschen Post AG, wie sie sich für die Haushalte darstellt, flächendeckend für Deutschland einzuschätzen. Dazu haben wir die Erreichbarkeit von Postämtern mit den Verkehrsmitteln Fuß, Fahrrad, Auto sowie mit dem öffentlichen Personen(nah)verkehr (ÖPNV) kleinräumig in einem 250250 Meter-Analyseraster mit Hilfe eines GIS-Erreichbarkeitsmodells aus der Perspektive der Haushalte untersucht. Dabei haben wir herausgefunden, dass Unterschiede in der Erreichbarkeit von Postämtern in Deutschland entgegen der landläufigen Meinung weniger ein räumliches Phänomen sind, das - wie oft angenommen - nicht-ländliche Regionen begünstigt und ländliche Regionen benachteiligt. Stattdessen zeigt unsere Studie, dass die Erreichbarkeit von Postämtern in Deutschland sowohl in ländlichen als auch in nicht-ländlichen Gebieten stark von der individuellen Mobilität der Menschen abhängt.
urn:nbn:de:gbv:253-202409-dn068781-3
Keywords: 630; Thünen-Erreichbarkeitsmodell; Postdienstleistungen; Deutschland; GIS; Erreichbarkeit; Thünen-Accessibility Model; post-market; Germany; accessibility